Surgical treatment of neuroendocrine neoplasms. (June 2021) - Clift, Ashley Kieran; Frilling, Andrea
Abstract: Surgery represents a fundamental component of treatment strategies in neuroendocrine neoplasms. Resection of the primary tumour, as well as locoregional and distant deposits, is currently the only modality possessing a chance of cure from neuroendocrine neoplasia disease. However, surgical intervention may also have legitimate palliative intents, such as cytoreduction of hormonally active tumour bulk that is not responsive to medical therapy and/or causes local symptoms. In some scenarios, such as in appendiceal neuroendocrine neoplasms, the adequate extent of surgery is debated. Increasingly, in advanced tumour stages, multimodal treatment approaches combining surgery with systemic targeted or liver-directed therapies to attain long-term control of disseminated disease are gaining rising attention.